The Effect of Sulphur Atom on the Structure of Biomolecule 2-Thiocytosine in the Gas-Phase, Solid-State, and Hydrated Forms and in DNA–DNA Microhelices as Compared to Canonical Ones - Mauricio Alcolea Palafox; Valentin Alba Aparicio; Sergio Toninelli Rodriguez; Josefa Isasi Marín; Jitendra Kumar Vats; Vinod Kumar Rastogi (Molecules)
This study is focused on the effects of the sulphur atom in position 2 of the cytosine molecule, 2-thiocytosine (2TC), on the molecular structural parameters in the isolated state, as well as in the hydration, solid state arrangement, Watson–Crick pairs, and DNA–DNA microhelices, as compared to the canonical form. The main six tautomers were optimised at the MP2 and CCSD levels, and the sulphur atom does not show any effect on the stability trend of cytosine. The energy difference between T2b and T2a tautomers is twice as low in 2TC (1.15 kJ/mol) than in cytosine (2.69 kJ/mol). The IR and laser Raman spectra of 2TC were accurately assigned using DFT computations and solid-state simulations of the crystal unit cell through several tetramer forms. The results notably improve those previously published by other authors. The effect of explicit water molecules surrounding 2TC up to 30, corresponding to the first and second hydration shells, on geometries and tautomerism was analysed. The Watson–Crick base pairs’ stability (ΔECP = −97.458 kJ/mol) was found to be less than with cytosine (−105.930 kJ/mol). The calculated dipole moment was also lower (4.205 D) than with cytosine (5.793 D). The effect of 2TC on the 5′-dG-dC-dG-3′ and 5′-dA-dC-dA-3′ DNA–DNA optimised microhelices was evaluated through their calculated helical parameters, which indicates a clear deformation of the helix formation. The radius (R) with 2TC appears considerably shorter (6.200 Å) in the 5′-dA-dC-dA-3′ microhelix than that with cytosine (7.050 Å). Because of the special characteristics of the 2TC molecule, it can be used as an anticancer drug.